Augmented reality, redefinition of visión and technology within art - Betanzos Torres, Eber Omar; Márquez Roa, Ubaldo (situArte, 2023)
The present essay focuses his study of the new technologies implemented in art, emphasizing the theme of the perception of images. Augmented reality and immersive art are ahead. Starting from an empirical approach and the observation technique, a first approach could made to the new variables that exist in the perception of the image through painting, which leads to the construction of reflections on the forms of artistic appreciation.